Real-time changes in brain activity during tibial nerve stimulation for overactive bladder: Evidence from functional near-infrared spectroscopy hype scanning - Li, Xunhua; Fang, Rui; Liao, Limin; Li, Xing (Frontiers in Neuroscience, 2023)
Purpose: To use functional near‐infrared spectroscopy (fNIRS) to identify changes in brain activity during tibial nerve stimulation (TNS) in patients with overactive bladder (OAB) responsive to therapy. Methods: Eighteen patients with refractory idiopathic OAB patients were recruited consecutively for this pilot study. At baseline, all patients completed 3 days voiding diary, Quality-of-Life score, Perception-of-Bladder-Condition, and Overactive-Bladder-Symptom score. Then 4 region-of-interest (ROI) fNIRS scans with 3 blocks were conducted for each patient. The block design was used: 60 seconds each for the task and rest periods and 3 to 5 repetitions of each period. A total of 360 seconds of data were collected. During the task period, patients used transcutaneous tibial nerve stimulation (TTNS) of 20-Hz frequency and a 0.2-millisecond pulse width and 30-milliamp stimulatory current to complete the experiment. The initial scan was obtained with a sham stimulation with an empty bladder, and a second was obtained with a verum stimulation with an empty bladder. Patients were given water till strong desire to void, and the third fNIRS scan with a verum stimulation was performed. The sham scan in SDV state requires the patient to hold urine again after urination to complete. NIRS_KIT software was used to analyze prefrontal activity, corrected by false discovery rate (FDR, p<0.05). Statistical analyses were performed using GraphPad Prism software; P< 0.05 was considered significant. Results: TTNS treatment was successful in 16 OAB patients and unsuccessful in 2. The 3 days voiding diary, Quality-of-Life score, Perception-of-Bladder-Condition, and Overactive-Bladder-Symptom score were significantly improved after TNS in the successfully treated group but not in the unsuccessfully treated group. The dorsolateral prefrontal cortex (DLPFC) and the frontopolar area (FA) were significantly activated during TNS treatment with an empty bladder rather than with an SDV. Compared with the successfully treated group, the unsuccessfully treated group did not achieve statistical significance with an empty bladder and SDV state. Conclusions: fNIRS confirms that TNS influences brain activity in patients with OAB who respond to therapy. That may be the central mechanism of action of TNS.